Assessment of saliva and gingival crevicular fluid soluble urokinase plasminogen activator receptor (suPAR), galectin‐1, and TNF‐α levels in periodontal health and disease. (13th March 2020) - Taşdemir, İsmail; Erbak Yılmaz, Huriye; Narin, Figen; Sağlam, Mehmet
Abstract: Objective: The aim of the study is to evaluate saliva and gingival crevicular fluid (GCF) levels of suPAR and galectin‐1 in different periodontal health status and relationship between these molecules and TNF‐α to understand the roles of these molecules in periodontal inflammation process. Background: Soluble urokinase plasminogen activator receptor (suPAR) has been described as a biological marker of inflammation and immunological activation. Galectin‐1, a member of the galectin family, is an anti‐inflammatory cytokine. However, to date, levels of these two molecules in periodontal health and disease have not been well documented. Methods: A total of 60 individuals, 20 with chronic periodontitis (group P), 20 with gingivitis (group G), and 20 with healthy periodontium (group H) were recruited for this study. Full‐mouth clinical periodontal measurements were recorded in periodontal charts. GCF and whole saliva samples were collected to determine the levels of suPAR, galectin‐1, and TNF‐α in study groups using enzymelinked immunosorbent assay (ELISA) method. Results: The GCF total amount of suPAR, galectin‐1, and TNF‐α in GCF was similar in group P and G ( P  > .05). The GCF total amounts of these molecules in GCF were higher in the group G and P compared to the group H ( P  < .05), whereas the GCF concentrations of suPAR and galectin‐1 were lower in the group G and P compared to the group H ( P  < .05).The saliva concentration of suPAR was significantly higher in group P compared to the group G and H ( P  < .05). It was also higher in the group G compared to the group H but there is no significant difference between the groups ( P  > .05). Salivary galectin‐1 levels were similar in the study groups ( P  > .05). Conclusion: Increased levels of GCF suPAR, galectin‐1, and saliva suPAR in periodontal disease suggest that these molecules may play a role in the periodontal inflammation. suPAR and galectin‐1 may be considered as potential biomarkers in periodontal disease.